Pemilihan Dan Penggunaan Media Pembelajaran PAI - Sania Junila; Hazizah Delpina; Gusmaneli Gusmaneli (CV. ITTC INDONESIA, 2025)
Islamic Religious Education (IRE) plays a central role in shaping students’ moral and spiritual character amid the challenges of the digital era. The selection and use of appropriatelearning media are key to creating an engaging, interactive, and meaningful learning process. This article outlines the principles of media selection, the criteria that must be considered, the types of relevant media, and optimal strategies for their use in the context of IRE. Based on a literature review and in-depth analysis, media such as animated videos, interactive applications, experience-based media can enhance students’ motivation and understanding by 40–60%. However, challenges such as limited technological infrastructure and insufficient teacher competence remain obstacles. This article offers practical recommendations, including teacher training, the development of media based on local culture, and the integration of technology that aligns with Islamic values.